Secondary structure components and properties of the melibiose permease from Escherichia coli: a fourier transform infrared spectroscopy analysis. - Dave, N (2000)
The structure of the melibiose permease from Escherichia coli has been investigated by Fourier transform infrared spectroscopy, using the purified transporter either in the solubilized state or reconstituted in E. coli lipids. In both instances, the spectra suggest that the permease secondary structure is dominated by alpha-helical components (up to 50%) and contains beta-structure (20%) and additional components assigned to turns, 3(10) helix, and nonordered structures (30%). Two distinct and strong absorption bands are recorded at 1660 and 1653 cm(-1), i.e., in the usual range of absorption of helices of membrane proteins. Moreover, conditions that preserve the transporter functionality (reconstitution in liposomes or solubilization with dodecyl maltoside) make possible the detection of two separate alpha-helical bands of comparable intensity. In contrast, a single intense band, centered at approximately 1656 cm(-1), is recorded from the inactive permease in Triton X-100, or a merged and broader signal is recorded after the solubilized protein is heated in dodecyl maltoside. It is suggested that in the functional permease, distinct signals at 1660 and 1653 cm(-1) arise from two different populations of alpha-helical domains. Furthermore, the sodium- and/or melibiose-induced changes in amide I line shape, and in particular, in the relative amplitudes of the 1660 and 1653 cm(-1) bands, indicate that the secondary structure is modified during the early step of sugar transport. Finally, the observation that approximately 80% of the backbone amide protons can be exchanged suggests high conformational flexibility and/or a large accessibility of the membrane domains to the aqueous solvent.